Rationale and design of the Sodium Lowering In Dialysate (SoLID) trial: A randomised controlled trial of low versus standard dialysate sodium concentration during hemodialysis for regression of left ventricular mass - Dunlop, JL; Vandal, AC; deZoysa, JR; Gabriel, RS; Haloob, IA; Hood, CJ; Matheson, PJ; McGregor, DOR; Rabindranath, KS; Semple, DJ; Marshall, MR (BioMed Central Ltd, 2013)
Background The current literature recognises that left ventricular hypertrophy makes a key contribution to the high rate of premature cardiovascular mortality in dialysis patients. Determining how we might intervene to ameliorate left ventricular hypertrophy in dialysis populations has become a research priority. Reducing sodium exposure through lower dialysate sodium may be a promising intervention in this regard. However there is clinical equipoise around this intervention because the benefit has not yet been demonstrated in a robust prospective clinical trial, and several observational studies have suggested sodium lowering interventions may be deleterious in some dialysis patients. Methods/Design The Sodium Lowering in Dialysate (SoLID) study is funded by the Health Research Council of New Zealand. It is a multi-centre, prospective, randomised, single-blind (outcomes assessor), controlled parallel assignment 3-year clinical trial. The SoLID study is designed to study what impact low dialysate sodium has upon cardiovascular risk in dialysis patients. The study intends to enrol 118 home haemodialysis patients from 5 sites in New Zealand over 24 months and follow up each participant over 12 months. Key exclusion criteria are: patients who dialyse more frequently than 3.5 times per week, pre-dialysis serum sodium of <135mM, and maintenance haemodiafiltration. In addition, some medical conditions, treatments or participation in other dialysis trials, which contraindicate the SoLID study intervention or confound its effects, will be exclusion criteria. The intervention and control groups will be dialysed using dialysate sodium 135mM and 140mM respectively, for 12 months. The primary outcome measure is left ventricular mass index, as measured by cardiac magnetic resonance imaging, after 12 months of intervention. Eleven or more secondary outcomes will be studied in an attempt to better understand the physiologic and clinical mechanisms by which lower dialysate sodium alters the primary end point. Discussion The SoLID study is designed to clarify the effect low dialysate sodium upon the cardiovascular outcomes of dialysis patients. The study results will provide much needed information about the efficacy of a cost effective, economically sustainable solution to a condition which is curtailing the lives of so many dialysis patients. Trial Registration Australian and New Zealand Clinical Trials Registry number: ACTRN12611000975998
Keywords: Home hemodialysis; Dialysis; Left ventricular mass; Sodium; Blood pressure; Fluid overload; Dialysate